The Search for Solidarity: The Industrial and Political Roots of the Cooperative Commonwealth Federation in British Columbia, 1913-1928 - Isitt, Benjamin (University of Victoria, 2003)
Born out of the industrial and political struggles of organized labour at the end of the First World War, the BC CCF was a product of organizational and ideological conflict in the 1910s and 1920s. This study explores the shift of BC socialism towards industrial action, which culminated in the One Big Union and the sympathetic strikes of 1919. It then examines the emergence of anti-Communism on the Left, shaped by the experience of political unity and disunity during the 1920s. These two factors fundamentally influenced the ideology and strategy adopted by the Cooperative Commonwealth Federation (CCF) in British Columbia. The ideological and tactical divisions of the 1930s were contested during the 1910s and 1920s. The collapse of the One Big Union, combined with deteriorating relations with the Communist Party, shifted BC socialists away from industrial militancy and toward parliamentary forms of struggle.